New frontiers in CRISPR: Addressing antimicrobial resistance with Cas9, Cas12, Cas13, and Cas14 - Ahmed S.A. Ali Agha; Ali Al-Samydai; Talal Aburjai (Heliyon)
Background: The issue of antimicrobial resistance (AMR) poses a major challenge to global health, evidenced by alarming mortality predictions and the diminishing efficiency of conventional antimicrobial drugs. The CRISPR-Cas system has proven to be a powerful tool in addressing this challenge. It originated from bacterial adaptive immune mechanisms and has gained significant recognition in the scientific community. Objectives: This review aims to explore the applications of CRISPR-Cas technologies in combating AMR, evaluating their effectiveness, challenges, and potential for integration into current antimicrobial strategies. Methods: We conducted a comprehensive review of recent literature from databases such as PubMed and Web of Science, focusing on studies that employ CRISPR-Cas technologies against AMR. Conclusions: CRISPR-Cas technologies offer a transformative approach to combat AMR, with potential applications that extend beyond traditional antimicrobial strategies. Integrating these technologies with existing methods could significantly enhance our ability to manage and potentially reverse the growing problem of antimicrobial resistance. Future research should address technical and ethical barriers to facilitate safe and effective clinical and environmental applications. This review underscores the necessity for interdisciplinary collaboration and international cooperation to harness the full potential of CRISPR-Cas technologies in the fight against superbugs.